Synthesis, Characterization and Electrochemistry of New Soluble Porphyrazine Complexes Bearing Octakis 3-Methylbutylthio Substituents - KOCA, ATIF (WILEY-V C H VERLAG GMBH, 2008)
Porphyrazines, MPz (M = Mg, H, Ni, Zn and Co) with octakis 3-methylbutylthio substituents have been synthesized starting with the corresponding unsaturated dicarbonitrile derivative. These new compounds have been characterized by UV-Vis. FTIR, H-1 NMR, MS and elemental analysis methods. Voltammetric properties of the complexes were also investigated by CV, DPV and CPC techniques. Electrochemical Studies show that three reversible one electron reductions and one reversible one electron oxidation processes (two for Co(II)Pz) are observed for all of the complexes. The E-1/2 values are similar for the H(2)Pz, Ni(II)Pz and Zn(II)Pz derivatives with negative shift due to the different effective nuclear charges of the central metal ion. Peak to peak separations and separation between the First reduction and first oxidation couples related with the HOMO-LUMO gap of the complexes are in harmony with the common porphyrazine complexes.
Keywords: Zinc; Cobalt; Nickel; Porphyrazines; Electrochemistry; ANNULATED DIAZEPINE RINGS; CRYSTAL-STRUCTURE; METAL; PHTHALOCYANINES; BEHAVIOR